2022
DOI: 10.1007/s11356-022-20387-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Sustainable impact of COVID-19 on education projects: aspects of naturalism

Abstract: History records show that pandemics and threats have always given new directions to the thinking, working, and learning styles. This article attempts to thoroughly document the positive core of coronavirus 2019 (COVID-19) and its impact on global social psychology, ecological stability, and development. Structural equation modeling (SEM) is used to test the hypotheses and comprehend the objectives of the study. The findings of the study reveals that the path coefficients for the variables health consciousness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 128 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…About CN 5128 billion is generated annually by China’s tourism industry. Even though Coronavirus had spread throughout the country, the tourism industry had been severely affected (Chang et al 2022 ; Pu et al 2022 ). The people have been ordered to stay home to protect themselves from the virus.…”
Section: Introductionmentioning
confidence: 99%
“…About CN 5128 billion is generated annually by China’s tourism industry. Even though Coronavirus had spread throughout the country, the tourism industry had been severely affected (Chang et al 2022 ; Pu et al 2022 ). The people have been ordered to stay home to protect themselves from the virus.…”
Section: Introductionmentioning
confidence: 99%
“…We could confirm our findings’ validity by modeling the regressions with other COVID-19 variables, such as COVID shocks (Sarkodie and Owusu 2021 ). In order to calculate COVID shocks, we use the gross export gap (also known as the export gap) (Pu et al 2022 ). The export gap was selected since it directly affects trade fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…This, however, quickly turned out to be not the case. "eradicating poverty and universal secondary education are unlikely to modify these emotions," argues Tang et al (2022). The well-off and the educated may be especially attuned to these emotions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Terrorists are not typically typical of the population; they are more likely to have higher levels of education and financial stability. Terrorists, according to Pu et al (2022), "are men and women in their twenties with some postsecondary degree, mainly in technical or engineering education." For instance, Worthington and Lee (2008) found that Al Qaeda members' biographies consistently revealed a high level of education, especially among the group's members involved in the sciences or the technological fields.…”
Section: Literature Reviewmentioning
confidence: 99%